Chemical ordering and relaxor properties in a novel solid solution of (1-x)Pb(Mg1/3Nb2/3)O3-xPb(Cd1/3Nb2/3)O3. (10th December 2019) - Liu, Zenghui; Wang, Caiyan; Zhang, Nan; Zhuang, Jian; Zhang, Jie; Ren, Wei; Ye, Zuo-Guang
Abstract: A novel relaxor solid solution of (1- x )Pb(Mg1/3 Nb2/3 )O3 - x Pb(Cd1/3 Nb2/3 )O3 [(1- x )PMN- x PCN] is synthesized by the solid-state reaction method. The crystal structure, electric properties and relaxor behavior are investigated. This system exhibits an average cubic perovskite structure at room temperature. The cation ordering, which is hardly detectable in the canonical PMN by laboratory-based high-resolution X-ray diffraction, is clearly evidenced in this solid solution. The relaxor behavior of the solid solution is found to be enhanced in the (1- x )PMN- x PCN solid solution compared with PMN. The enhanced relaxor behavior is attributed to be formation of complex ordered and disordered structures, which leads to a broader distribution of the size and dynamics of local polar heterogeneities.